2018
DOI: 10.1186/s12981-018-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Linking gender, extramarital affairs, and HIV: a mixed methods study on contextual determinants of extramarital affairs in rural Tanzania

Abstract: BackgroundExtramarital sex is a potential driver of human immunodeficiency virus (HIV) transmission for long-term couples in sub-Saharan Africa. It is increasingly recognized that preventing sexual risk behaviours requires an understanding and adjustment of sexual relationship factors beyond the individual level. We investigated the association between extramarital affairs and HIV status, factors associated with extramarital affairs, and created insights in the context and pathways for married men and women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Power inequities in relationships were reported -women interpreted some of the men's behaviour as holding a patriarchal position while men also perceived social undermining by wives. These were also noted by Leburu-Masigo (2019) and Mtenga et al (2018). This study further shows that retaliation by both husbands and wives, as well as the victims' next-of-kin exacerbated the incidents.…”
Section: Discussionsupporting
confidence: 76%
“…Power inequities in relationships were reported -women interpreted some of the men's behaviour as holding a patriarchal position while men also perceived social undermining by wives. These were also noted by Leburu-Masigo (2019) and Mtenga et al (2018). This study further shows that retaliation by both husbands and wives, as well as the victims' next-of-kin exacerbated the incidents.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the conviction that someone using contraceptive methods is susceptible to being unfaithful is another limiting factor to use FP 28. When a married woman uses contraceptive methods (mainly without her partner’s knowledge) that implies she has extraconjugal affairs and does not want to be caught with an unexpected pregnancy 28 50. However, previously, researchers highlighted that some women are ready to use contraceptive methods without their partner’s knowledge27 to protect themselves from approaching births and consequences.…”
Section: Discussionmentioning
confidence: 99%
“…We found that men were more likely to have experienced anal sex, transactional sex, have multiple sexual partners, and use condoms (Table 1). Gender differences in sexual practices have been established in similar populations [12]. The influence of sociodemographic characteristics on the relationship between sexual behavior and HIV status was explored in a better fitting model that adjusted for these characteristics.…”
Section: Discussionmentioning
confidence: 99%